KONSELING INDIVIDU KONSELING INDIVIDU DENGAN PENDEKATAN CBT UNTUK MEREDUKSI KECEMASAN SOSIAL REMAJA - Zhenata Andiny (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
Social anxiety is the fear of social situations in interacting with others that can lead to feelings of fear, inferiority, negative judgment and judgment. This study aims to determine the problem of social anxiety experienced by one of UIN Cyber Sheikh Nurjati Cirebon students before and after individual counseling with CBT approach. Counseling with CBT approach is an effort to modify the function of thinking, feeling, and acting. This research uses a qualitative approach with a case study type of research. Case study is one part of a qualitative research method that focuses on a case intensively and in detail. Based on the research conducted, the client initially had symptoms that led to social anxiety such as difficulty interacting with his environment, being easily pessimistic, worrying about the judgment of others, lack of confidence, and tending to close himself. After individual counseling with a CBT approach, the client begins to have the will and can act on what has been agreed upon during the counseling session. Keyword: Individual Counseling, Social Anxiety, CBT